ALTERATIONS IN SOME COAGULATION BIOMARKERS OF PULMONARY TUBERCULOSIS SUBJECTS IN THE SETTINGS OF HUMAN IMMUNODEFICIENCY VIRUS INFECTION: AS SEEN IN MAIDUGURI NORTH EASTERN NIGERIA - Obi SO; Bukar A; Amilo GI; Digban KA; Medugu JT; Waziri G; Osakue EO; Peyo BA; Abja UM; Olaniyam MF; Jeremiah ZA (Ntec Specialist, 2016)
Background: Synergistic association between Human Immunodeficiency virus (HIV) and pulmonary tuberculosis (PTB) infection has resulted in variable haematological manifestations including coagulopathies; these accelerated the morbidity and mortality burden of HIV/PTB coinfection. Objectives: Based on this preposition, we prospectively evaluated some coagulation biomarkers in a case-controlled study of 102 HIV sero-positive subjects consistent with WHO clinical stages I and II, 56 HIV/PTB co-infected subjects; both groups were therapy naive. Also 104 HIV seronegative healthy blood donors were recruited as control subjects. Method: All participants were tested for platelet count (PLT), Plasma fibrinogen concentration (PFC), Protein C (PC), prothrombin time (PT) and Activated partial thromboplastin time (APTT). Results: In HIV/PTB co-morbidity PT, APTT were prolonged (P less than 0.001); PLT and PFC were also elevated (P less than 0.001), while PC % activity was down-regulated (P less than 0.01) all in comparison to the HIV group and the controls. Conclusion: We asserted that alterations occur in some coagulation indices of PTB/HIV coinfected individuals found in our environment. Clinical findings are however, needed to shed more light on these findings to aid patient's management